2007
DOI: 10.1109/iembs.2007.4352552
|View full text |Cite
|
Sign up to set email alerts
|

Determination of simple thresholds for accelerometry-based parameters for fall detection

Abstract: The increasing population of elderly people is mainly living in a home-dwelling environment and needs applications to support their independency and safety. Falls are one of the major health risks that affect the quality of life among older adults. Body attached accelerometers have been used to detect falls. The placement of the accelerometric sensor as well as the fall detection algorithms are still under investigation. The aim of the present pilot study was to determine acceleration thresholds for fall detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
135
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(144 citation statements)
references
References 16 publications
4
135
0
Order By: Relevance
“…Typical approach is detection of falls by applying thresholds to accelerations, velocities and angles [7]. In [12] they used a 3-axis accelerometer worn on the chest; by applying a simple threshold to the acceleration, they detected falls with 98.9% accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…Typical approach is detection of falls by applying thresholds to accelerations, velocities and angles [7]. In [12] they used a 3-axis accelerometer worn on the chest; by applying a simple threshold to the acceleration, they detected falls with 98.9% accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…A postural change detection sensor module (PCDSM) was developed to investigate postural changes and movement patterns in ADL events and falls [11]. Bourke to be the best position for attaching the tri-axial accelerometer [12], whereas Kangas et al reported the waist to be the best position [13]. Other researchers too suggested the chest (or trunk)…”
Section: Itroductionmentioning
confidence: 99%
“…A very well addressed sub-task of Health Condition is the fall detection in which accelerometers are seen as the suitable technology. [17], [11], [57], [73], [65], [55], [16], [74], [56], [130], [137], [119]; A B [82]; 2xA B [23]; G [18]; AG [64] Floor vibration-based sensor [4]; array of acoustic sensors [94]; Tilt sensor + piezoelectronic A + vibration sensor [83]; tri-axial MTx [134]; A T +G T [50], [127]; multiple A T [44]; A T +BAR [114] Kin [72], [90]; Cam [101], [7], [41] IR, pressure sensor, audio…”
Section: Physiological Health Condition and Healthcarementioning
confidence: 99%